Seguimento nutricional de pacientes após episódios de lesão renal aguda e identificação de fatores de riscos nuricionais para o óbito tardio - Xavier, Patricia Santi [UNESP] (2015)
Introduction: The prognosis of Acute Kidney Injury (AKI) is poor, with early mortality rate from 40% to 80% and late mortality between 15 and 72%. The negative impact of malnutrition on the early outcome of AKI patients has recently been confirmed by various studies. However, nutritional evaluation after discharge of critically ill patients has not been studied. The aim of the study was to evaluate the nutritional status of patients after an episode of AKI and identify nutritional markers associated with late death in these patients. Methods: Prospective cohort study was performed with patients older than 18 years diagnosed with renal or post-renal AKI and followed up by AKI team, Department of Internal Medicine, Botucatu School of Medicine and underwent complete nutritional assessment that included anthropometry, food intake, bioimpedance, biochemical tests, handgrip, anamnesis and subjective global assessment. It was performed in two moments at hospitalization (at the beginning and end of nephrologist evaluation) and in three moments after hospital discharge (at 1 month, 3 and 6 months). Results: We included 95 patients, age of 62.3 ± 14.7 years, prevalence of hospitalization in medical wards of 71.6%, index of severity of AKI (ATN-ISS) of 28%, early and late mortality rates were 13.6 and 25.6%,respectively. Risk factors associated with early mortality were AKI severity (HR=1.89, 95%CI= 1.48-3.46, p=0.04), no recovery of renal function (HR=1.46, 95%IC=1.02 - 2.16, p=0.03), severe weigh loss (HR=1.95, 95%CI= 1.19-3.3, p=0.02), reactance at first moment of nephrologist evaluation (HR=1.51, 95%CI=1.04-1.91, p=0.01) and albumin at last nephrologist evaluation (HR=1.41, 95%CI=1.04-1.61, p=0.01). weight variation between time of first evaluation by a nephrologists and after 1 month of outpatient follow-up (71.10 ± 19.43 x 71.66 ± 21, p = 0.02) and with late mortality the number of comorbidities (HR=1.79, 95%CI=1.45-2.46, p=0.04), cancer ...